Interval Oscillation Criteria for Super-Half-Linear Impulsive Differential Equations with Delay - Zhonghai Guo; Xiaoliang Zhou; Wu-Sheng Wang (Journal of Applied Mathematics)
We study the following second-order super-half-linear impulsive differential equations with delay [r(t)φγ(x′(t))]′+p(t)φγ(x(t-σ))+q(t)f(x(t-σ))=e(t), t≠τk, x(t+)=akx(t), x′(t+)=bkx′(t), t=τk, where t≥t0∈ℝ, φ*(u)=|u|*-1u, σ is a nonnegative constant, {τk} denotes the impulsive moments sequence with τ1<τ2<⋯<τk<⋯, lim k→∞τk=∞, and τk+1-τk>σ. By some classical inequalities, Riccati transformation, and two classes of functions, we give several interval oscillation criteria which generalize and improve some known results. Moreover, we also give two examples to illustrate the effectiveness and nonemptiness of our results.